Revisiting Job Satisfaction and Intention to Stay: A Cross-sectional Study among Hospital Nurses in the Philippines - Sapar, Lester Canarejo; Oducado, Ryan Michael F. (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: The global shortage of nurses and the rapid turnover of nurses remain crucial issues and areas of concern that call for immediate attention. Job satisfaction is a recognized determinant of nurses’ decision to stay in their current workplace. However, while nurses’ job satisfaction has received considerable attention among scholars, the results of studies are still mixed.Purpose: The purpose of this study was to revisit and assess the job satisfaction and intention to stay of nurses in two selected hospitals in the Philippines.Methods: A cross-sectional research design was used in this study. A sample of 120 nurses in a public and private hospital in the Philippines responded to the Job Satisfaction Survey and Intent to Stay Scale questionnaires. Descriptive statistics, t-test, one-way ANOVA, and Pearson’s r were employed for data analysis.Results: Results show that the majority (58.3%) of the nurses were neither satisfied nor dissatisfied with their job. Also, nurses intended to neither stay nor quit in their current workplace with only a few (9.2%) had high intention to stay. Nurses were most satisfied in terms of the nature of their job (18.95+2.50) but were dissatisfied with the fringe benefits (12.69+4.11) and operating conditions (12.18+2.58) at work. Nurses in the public hospital (p=0.040) and those with higher salaries (p=0.015) had significantly higher intentions to stay. Job satisfaction and intention to stay were significantly related (p=0.002).Conclusion: Nurses’ job satisfaction is positively linked with their intention to stay in their current workplace. This study highlights that efforts should be made to improve nurses’ job satisfaction to encourage nurses to remain in their current workplace. Also, increasing nurses’ salary particularly those nurses in the private sector is a focal point of consideration to ensure that there is enough supply of nurses in the country.